Method of determination of survival characteristics of weapons and military equipment - Dachkovskyi , Volodymyr (Social Development and Security, 2020)
In order to repel armed aggression in the East of Ukraine, the national defense-industrial complex has modernized and developed a significant nomenclature of weapons and military equipment, which correspond to the forms and methods of conducting modern hostilities. Experience of using the samples of weapons and military equipment, which are allowed to exploitation in the Armed Forces of Ukraine, indicates on the necessity of resolving a number of problematic issues related to tecnical maintenance, repair, providing of logistical means etc., for keeping them in working orderKeeping the samples of weapons and military equipment in working order in conditions of fightfare is determined by the number of factors, the one of which is their survivability, namely ability of sample of weapons and military equipment to keep their parameters in given limits,withstand damage of all kinds, and in the event of damage retain the possibility of combat use after repair with minimal cost of time and repair.The article proposes a technique for determining the survivability characteristics of a sample of weapons and military equipment. This technique makes it possible to determine the durability and reproducibility indices of weapons and military equipment samples thereby determining the survivability of a particular weapons and military equipment sample or group of single-purpose machines.